Emotional expression in vocal skill from the perspective of multiculturalism - Wang, Di (Música Hodie, 2022)
The research is devoted to study the influence of emotional singing on the listeners' perception of vocal mastery in the process of intercultural musical dialogue. In the context of studying the influence of emotional singing on the quality of perception by listeners, an experiment was conducted; it involved 11 student vocalists from China, Russia, Italy, Brazil, Azerbaijan, Hungary, Greece, India, Canada, Korea, Nigeria, 5 independent listeners, and 5 music experts. The analytical experiment created an opportunity to reveal the impact of the vocalist's emotional expression when performing a national folk song on the listener perception. The percentage of coherence between emotional production and listener perception ranged from 62.8% to 76.2%. Vocal skills of a singer can reveal the emotional aspects of a piece of music to the public, which are of great value in contemporary art; they determine the popularity of a performer on the world stage.